1972
DOI: 10.1017/s1120962300024318
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Pregestational Weight and Multiple Pregnancy Duration

Abstract: Statistical studies have shown a significant correlation between maternal pregestational weight and duration of pregnancy (i.e., a low weight may cause a shortening of pregnancy). Duration of pregnancy is further correlated to the weight gain (i.e., it is shortened by an insufficient gain). This phenomenon is observed in thin women, but not in women of heavy weight before the pregnancy.The studies of weight losses obtained through hypocaloric or sodium-free diets or diuretics, show that a sudden weight loss ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

1981
1981
2003
2003

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…This is not applied for single pregnancies, where ultrasounds are only proposed when a specific indication is present. But for twin pregnancies, clinical surveillance and hormonal assays are of little or no value [11]. Intrauterine growth retardation is diagnosed when the physical values -biparietal, transverse, abdominal and femur length -are under the 10th centile of locally established curves for twin pregnancies [5].…”
Section: Methodsmentioning
confidence: 99%
“…This is not applied for single pregnancies, where ultrasounds are only proposed when a specific indication is present. But for twin pregnancies, clinical surveillance and hormonal assays are of little or no value [11]. Intrauterine growth retardation is diagnosed when the physical values -biparietal, transverse, abdominal and femur length -are under the 10th centile of locally established curves for twin pregnancies [5].…”
Section: Methodsmentioning
confidence: 99%
“…Weight loss needs to be avoided in multiple pregnancies. Konwinski et al (1973) reported that twins were three times more likely to be born prematurely to women of any weight who lost weight after 28 weeks gestation.…”
Section: Weight Gainmentioning
confidence: 99%